Cities and water: A fluvial and environmental analysis of Espinharas River in Patos city, Paraíba State - Silva, Emmanoel Marques da; Carvalho, Gabriel Lincoln Lopes; Silva , Paulo Roberto de Oliveira; Silveira, José Augusto Ribeiro da; Canova, César Renato (National Journal of City Management, 2022)
The urbanization process over the last 70 years has provided cities with a distance from their relationship with the natural elements that comprise their surroundings and urban formation. Highlights include urban rivers that have mainly been deteriorated and forgotten by the population. Rivers have always been linked to the history and development of cities, but this relationship has led to conflicts over the years, starting a process of degradation that has culminated in deteriorating the relationship between rivers and cities. Based on this, the present work aims to analyze the fluvial and environmental conditions of a stretch of the Espinharas River in Patos city, Paraíba State, pointing out its weaknesses and potential. Based on the results obtained, a framework is proposed with guidelines capable of establishing this connection between the urban and natural environment, based on a tripod formed by the integration of the river with the city, recovery of its waters, and raising the population´s awareness of the importance from the river to the local quality of life. The research uses the hypothetical-deductive method, and its methodological steps are performed in three phases: the first is the literature review; the second, diagnosing the stretch of the river under analysis; and the last step addresses the construction of the framework of the guidelines. Finally, an understanding of the current situation of the stretch of the Espinharas River under analysis and the hypothetical effects of applying all selected guidelines is obtained, thus contributing to the qualification of relationship between the river and cities.